A competitive equilibrium for a warm glow economy - Nizar Allouch (Queen Mary University of London, Department of Economics, 2009)
Despite a widespread interest in the warm glow model [Andreoni (1989,1990)], surprisingly most attention focused on the voluntary contribution equilibrium of the model, and only very little attention has been devoted to the competitive equilibrium. In this paper, we introduce the notion of competitive equilibrium for a warm glow economy [Henceforth, warm glow equilibrium]. Then, we establish (and prove), in the contest of our model, the three fundamental theorems of general equilibrium: (i) warm glow equilibrium exists; (ii) a warm glow equilibrium is Pareto efficient; and (iii) a Pareto efficient allocation can be decentralized as a warm glow equilibrium). The concept of a warm glow equilibrium may prove to be very useful to the normative and positive theory of public goods provision. First, it is a price based mechanism achieving efficient outcomes. Secondly, not only the warm glow equilibrium outcomes could serve as a point of reference to measure free-riding and welfare loss, but also due to warm glow effects, unlike Lindahl allocations, they are more likely to be achieved.
Keywords: H41; D64; C62; 330; warm glow; altruism; competitive equilibrium; free riding; public goods provision; Gleichgewichtstheorie; Altruismus; Trittbrettfahrerverhalten; Öffentliches Gut; Theorie